THE MIDDLE TRIASSIC LAGERSTÄTTE OF MONTE SAN GIORGIO REVEALS THE OLDEST LACE BUGS (HEMIPTERA: TINGIDAE): ARCHETINGIS LADINICA GEN N. SP N. (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
A new genus and species of fossil lace bugs (Hemiptera; Tingidae), Archetingis ladinica gen. n. et sp. n. is described from the lower Kalkschieferzone (Meride Limestone, Upper Ladinian) of the Swiss side of Monte San Giorgio. The new taxon clearly resembles modern Tingidae in its hemelytra and pronotum, with two rows of areole, in the presence of bucculae closed at the anterior end, not extending beyond the apex of the head, and in the presence of a labial groove on the meso-/metathoracic sternum. Distinctive features are the thick femurs of the first and second pair of legs, the exceptional size (total length of ~12 mm) if compared with both fossil and extant species. Archetingis ladinica gen. n. et sp. n. represents by far the oldest known species of this family and brings back the origin of Tingidae of approximately 140 My, well into the Middle Triassic. The discovery of A. ladinica, beside its evolutionary consequences on the origin of extant Tingidae, provides evidences for the presence of terrestrial ecosystems nearby to the depositional environment. According to the living and trophic behavior of extant Tingidae, those emerged lands had to be covered by vegetation.